Marijuana use and visual performance in sport - Grill-Donovan, K. (2018)
It is estimated that 80% of the sensory information around you is processed by your visual system. Therefore, any change or decrease in the functioning of these visual pathways can have a significant impact on your performance. Additionally, the ease of obtaining marijuana in Canada makes it very important for patients, and high performance athletes to understand the effects it could have.